Grocott Methenamine Silver Staining Is the Optimal Approach to Histological Diagnosis of Pulmonary Cryptococcosis - Wang, Suijing; Lai, Jieyi; Wu, Ruibin; Zhang, Lihong; Huang, Mayan; Xiao, Yongbo; Zhang, Xinke; Chen, Jiewei (Frontiers in Microbiology, 2022)
Background: Histological staining methods for Cryptococcus identification vary in accuracy. This study aimed to investigate the clinical value of Grocott methenamine silver(GMS), periodic acid-Schiff (PAS), and Alcian blue (AB) staining in the diagnosis of pulmonary cryptococcosis(PC). Methods: From April 2004 to June 2021, the clinical and pathological data of 152 patients with PC were collected from the Department of Pathology, Sun Yat-sen University Cancer Center. The sensitivity and identifiability of GMS, PAS, and AB staining for histological diagnosis were systematically evaluated using statistical methods combined with the microscopic characteristics of PC cases. Results: Statistical analysis showed that the detection rates of GMS,PAS, and AB staining were 100.0%(152/152), 94.7%(144/152), and 81.6%(124/152), respectively. McNemar's test showed that the sensitivity of GMS was significantly higher than those of PAS (P=0.008) and AB stains (P<0.001).Both PAS and AB stains had obvious non-specific staining,which interfered with the detection of Cryptococcus, and increased diagnostic difficulties. In contrast, in GMS staining, Cryptococcus spores were prominent with a clean background and were clearly observed at low or medium power magnification, with the identifiability significantly better than those of PAS or AB staining. Conclusions: GMS staining had sensitivity up to 100%, and identifiability that was better than those of PAS and AB staining. GMS is the best method for histological diagnosis of pulmonary cryptococcosis.